Training on The Application of Nebulisation with The Semi Fowler Position in Controlling The Breath Frequency of Bronchial Asthma Patients At The GM Hospital - Purba, Anita Gandaria; Simanjuntak, Elfrida; Ginting, Samuel; Kalvin, Freddy (JURNAL PENGMAS KESTRA (JPK), 2024)
Respiratory disorders can attack anyone indiscriminately. It is often found that types of respiratory diseases such as asthma and ARI. The causes are varied, such as dirty air, bacteria, and viruses. The world death rate of 20% is caused by asthma which is estimated for the next 10 years if it is not treated properly. Bronchial asthma is a type of non-communicable but chronic disease of varying severity in the respiratory tract. Pharmacological therapy such as nebulization and non-pharmacological therapy such as the semi-Fowler position are appropriate treatments to be given to patients with bronchial asthma so that they can regulate the patient's respiratory frequency. Giving a nebulizer can overcome shortness of breath, relax bronchial spasms, liquefy phlegm, and clear the airways. Meanwhile, the semi-Fowler position can provide comfort in breathing so that the lungs become wider. This training activity was attended by PkM participants, namely 20 nursing staff. The series of PkM activities include the delivery of material, discussions, therapy demonstrations, and simulations of treating bronchial asthma patients using nebulization and the semi-Fowler position. The media used are a nebulizer, teaching aids, and SOP. The results of the PkM implementation show that the PkM participants have understood the benefits of nebulization in the semi-Fowler's position. Apart from that, PkM participants were also able to carry out the two treatments by the SOP which was implemented through simulation.